Assessment of a glyoxalase I frameshift variant, p.P122fs, in Japanese patients with schizophrenia. (October 2018) - Ishizuka, Kanako; Kimura, Hiroki; Kushima, Itaru; Inada, Toshiya; Okahisa, Yuko; Ikeda, Masashi; Iwata, Nakao; Mori, Daisuke; Aleksic, Branko; Ozaki, Norio
Abstract : Enhanced carbonyl stress has been observed in a subgroup of patients with schizophrenia. Glyoxalase I, which is encoded by GLO1, is an enzyme that protects against carbonyl stress. In this study, we focused on the association between rare genetic variants of GLO1 and schizophrenia. First, we identified one heterozygous frameshift variant, p.P122fs, in 370 Japanese schizophrenia cases with allele frequencies of up to 1% by exon-targeted mutation screening of GLO1 . We then performed an association analysis on 1282 cases and 1764 controls with this variant. The variant was found in three cases and eight controls. There was no statistically significant association between p.P122fs in GLO1 and schizophrenia ( P =0.25). This frameshift variant in GLO1 might occur at near-polymorphic frequencies in the Japanese population, although further investigations using larger samples and biological analyses are needed to exclude the possibility of a low-penetrance genetic risk associated with this variant.